Prevalence and risk factors for falls among community-dwelling adults in Riyadh area - Alenazi,Aqeel M.; Alanazi,Maram F.; Elnaggar,Ragab K.; Alshehri,Mohammed M.; Alqahtani,Bader A.; Alhowimel,Ahmed S.; Alhwoaimel,Norah A.; Alanazi,Ahmad D.; Alotaibi,Mazyad A.; Almutairi,Sattam M.; Alghamdi,Mohammed S.; Bindawas,Saad M. (PeerJ, 2023)
Objectives This study aimed to assess fall prevalence, identify related risk factors, and establish cut-off scores for fall risk measures among community-dwelling adults in Riyadh region of Saudi Arabia. Methods A cross-sectional study was conducted in community, Riyadh city, Saudi Arabia. A sample of 276 Saudi citizens aged ≥40 years who were able to read and write in Arabic. Fall history and number of falls in the past 12 months were determined via self-reports. Variables assessed included demographic information, self-reported chronic diseases, depressive symptoms, and back pain severity. Results Participants were classified as either fallers (n = 28, 10.14%) or non-fallers. Fallers were more likely to have arthritis (odds ratio [OR]: 7.60, p = 0.001), back pain (OR: 5.22, p = 0.002), and higher depressive symptom scores (OR: 1.09, p = 0.013) than non-fallers. The number of reported falls was significantly associated with an elevated body mass index (incidence rate ratio [IRR]: 1.09, p = 0.045), arthritis (IRR: 8.74, p < 0.001), back pain (IRR: 4.08, p = 0.005), neurological diseases (IRR: 13.75, p < 0.007), and depressive symptoms (IRR: 1.08, p = 0.005). Cut-off scores predictive of falls associated with back pain and depressive symptoms were 1.5 (sensitivity: 0.61; specificity: 0.79; area under the curve [AUC]: 0.70) and 11.5 score (sensitivity: 0.57; specificity: 0.76; AUC: 0.66), respectively. Conclusions The prevalence of falls was relatively low among the individuals considered in this study. Chronic conditions, back pain severity, and depressive symptoms were determined to be associated with falls among community-dwelling individuals in Saudi Arabia.
Keywords: Falling; Mental health; Falls; Middle aged; Elderly; Depressive symptoms; Chronic disease; Chronic illness